Relation of vitamin D deficiency with maternal morbidity - Yusuf, Ahmad Yusuf; Yazaje, Haytham; Kserawy, Mawia (Latakia University Journal -Medical Sciences Series, 2018)
Appear To The Researchers In Department Of Obstetrics And Gynecology Rising Of Morbidity At Pregnancies Because Of Vitamin.D Deficiency , Which There Is Positive Relation Between The Level Of Vitamin .D And Complication Of Pregnancy Such As Preeclampsia , Gestational Diabetes , Preterm Birth , Premature Baby And Small Birth Weight . To Determine The Relationship Between Vitamin D Deficiency And Maternal Morbidity At Tishreen University Hospital. We Measured The Maternal Level Of 25-(Oh)D3 For 158 Pregnant "Pregnancy Age<32 Weeks" Divided Into Five Groups: Preterm Labor "40 Patients", Pre Eclampsia "35 Patients", Gestational Diabetes "18 Patients", Low Birth Weight "25 Patients" And The Control Group "40 Patients". The Mean Of 25-(Oh)D3 In Control Group Was Higher Than Others. The Differences Were Significant (P<0.05). Preterm Labor Group: 20% Of Patients Have 25-(Oh)D3 Deficiency, And Gestational Age At Birth Lower. Pre Eclampsia Group: 20% Have 25-(Oh)D3 Deficiency, And The Blood Pressure Was Significantly Higher. Gestational Diabetes Group: 22.2% Of Them Have 25-(Oh)D3 Deficiency With Higher Levels For Fasting Glucose. Low Birth Weight Group 28% Have 25-(Oh)D3, Whereas The Control Group Had 2.5% 25-(Oh)D3 Deficiency. Vitamin D Deficiency Accompany With Adverse Obstetrical Morbidity علاقة نقص الفيتامين. د بالمراضة الحملية التوليدية تبيّن لدى الباحثين في مجال التوليد وأمراض النساء ارتفاع المراضة لدى الحوامل بسبب تدني قيمة الفيتامين د، وتوضحت علاقة إيجابية بين مستوى الفيتامين د ومشاكل الحمل مثل ما قبل الإرجاج والسكري الحملي والولادات الباكرة وما يرافقها من خداج بالإضافة لصغر وزن الولادة. وهدف البحث لتحديد العلاقة ما بين نقص الفيتامين د والمراضة الحملية التوليدية في مشفى تشرين الجامعي باللاذقية. تمت معايرة مستوى 25(OH)D3 الوالدي لدى 158 سيدة حامل أقل من 32 أسبوع مقسمة إلى خمس مجموعات: مخاض مبكر "40 مريضة"، ماقبل إرجاج "35 مريضة"، سكري حملي "18 مريضة"، وجود وزن ولادة منخفض "25 مريضة"، والمجموعة الشاهد "40 مريضة". كان المتوسط الحسابي لـ 25(OH)D3 أعلى بشكل هام في مجموعة الشاهد مقارنة بباقي المجموعات المرضية (P<0.05). في مريضات المخاض المبكر: 20% من المريضات لديهن عوز 25(OH)D3، وكان العمر الحملي للولادة أقل. مريضات ما قبل الإرجاج: 20% عوز 25(OH)D3 وكان الضغط الشرياني أعلى بشكل هام عندهن. مريضات السكري الحملي: 22.2% عوز 25(OH)D3 مع قيم أعلى للسكري الصيامي. وزن ولادة منخفض: 28% عوز 25(OH)D3. بينما المجموعة الشاهدة 2.5% يوجد عوز 25(OH)D3 وتبين أن عوز فيتامين د يترافق مع مراضة توليدية سيئة.